Retrospective Drug Use Evaluation of Gentamycin Use in Ambo Hospital, Oromia Region State, West Showa, Ethiopia - Gelaw, Belayneh Kefale; Tegegne, Gobezie Temesgen; Defersha, Amsalu Degu; Legese, Alemitu (Indian Journal of Pharmacy Practice)
Drug should be used appropriately, safely and only when needed 50% or more of drug expenditure may be wasted through irrational prescribing, dispensing and patient use of drugs. Drug use evaluation is one of the useful methods to evaluate the rational use of drug in health institution and has performance of improved method that focus evaluation and improving medication use process with the goal of patient outcome. The objective of this study will to evaluate the rational use of gentamycin in Ambo Hospital. Retrospective systematic study was used to assess rational use of Gentamicin. The study was conducted by reviewing medication records of 400 patients, who received Gentamicin during hospitalization in Ambo general Hospital from Jan.1, 2013-Jan, 1, 2014. A systematic sampling method was used to select prescriptions in this hospital with Gentamicinand patient cards were located based on the medical record number on the prescription papers. Data was collected by using structured format and evaluated against WHO criteria for drug use evaluation as per standard treatment guideline of Ethiopia.Most patients were dosed as 5mg/kg/day (59%). The duration of therapy was found to be high in the range 2-7 days (64.25%). Gentamicin was mainly used as pneumonia treatment (36%). Maintenance fluids were the most commonly co-administered medications with a frequency of 67.75%. The use of Gentamicin was appropriate only in 189 cases (47.25%) for the justification of use. Most of inappropriate uses were seen in terms of duration during treatment of pneumonia followed by frequency for the treatment of AGE. Consistency of prescriber to the national standard treatment guideline was found to be low.To improve rational use and prevent the development of resistance; prescribers should adhere to the national standard treatment guideline. Intensification of short-term trainings and antibiotic control systems are some of the possible solutions the hospital has to do.Gentamicin therapy does not meet the current STG of Ethiopia.
Keywords: Drug Use Evaluation; Gentamicin; Ambo